2014
DOI: 10.1111/ger.12167
|View full text |Cite
|
Sign up to set email alerts
|

Failure rates of class V restorations in the management of root caries in adults – a systematic review

Abstract: There is a need for more research in this area as many of the studies identified in this systematic review treated post-radiation, xerostomic patients which are not typical of the general population. Increased adherence to CONSORT guidelines for reporting is also advised to facilitate future systematic review and meta-analysis in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Crowns were assumed to require renewal every 12 y (Lucarotti and Burke 2009). For root surface restorations, a replacement every 4 y was assumed (Hayes et al 2016). 2) Prosthetic services: MT were assumed to require a prosthetic tooth replacement therapy, with MT ≤ 4 requiring a fixed dental prosthesis, and MT > 4 a removable dental prosthesis according to the regulations of the statutory health insurance in Germany (KZBV 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Crowns were assumed to require renewal every 12 y (Lucarotti and Burke 2009). For root surface restorations, a replacement every 4 y was assumed (Hayes et al 2016). 2) Prosthetic services: MT were assumed to require a prosthetic tooth replacement therapy, with MT ≤ 4 requiring a fixed dental prosthesis, and MT > 4 a removable dental prosthesis according to the regulations of the statutory health insurance in Germany (KZBV 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Further trials should account for the expectedly high attrition rates in the target population in their power calculation. Third, the failure rates of both ART and CT restorations were high, which illustrates the challenges of restoring root caries lesions in institutionalised older patients and calls into question if restorative approaches in these situations are generally an appropriate therapy. Alternative non‐invasive treatment options (eg application of silver diamine fluoride (SDF)) may be effective for managing root caries lesions without restoring them .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the failure rates of both ART and CT restorations were high, which illustrates the challenges of restoring root caries lesions in institutionalised older patients 32 and calls into question if restorative approaches in these situations are generally an appropriate therapy.…”
Section: Due To Its Reduced Instrumental and Technical Requirementsmentioning
confidence: 99%
“…However, previous studies indicated that a commercial resin-modified glass ionomer was not potent enough to inhibit bacterial growth and biofilm formation [22]. In addition, glass ionomer cement was relatively less esthetic for anterior teeth and cervical lesions [50]. Therefore, the present study focused on developing an antibacterial and remineralizing composite for Class V restorations, because it is highly desirable to develop a novel multifunctional composite for Class V restoration to achieve remineralization to strengthen and protect the root structures, while being able to inhibit cariogenic and periodontitis-related pathogens.…”
Section: Discussionmentioning
confidence: 99%